Myocardial Injury and Prognosis in Hospitalized COVID-19 Patients in Brazil: Results From The Brazilian COVID-19 Registry - Barbosa, Hannah Cardoso; Martins, Maria Auxiliadora Parreiras; de Jesus, Jordana Cristina; Meira, Karina Cardoso; Passaglia, Luiz Guilherme; Sacioto, Manuela Furtado; Bezerra, Adriana Falangola Benjamin; Schwarzbold, Alexandre Vargas; Maurílio, Amanda de Oliveira; Farace, Barbara Lopes; da Silva, Carla Thais Cândida Alves; Cimini, Christiane Corrêa Rodrigues; et al. (Sociedade Brasileira de Cardiologia, 2023)
Background: Cardiovascular complications of COVID-19 are important aspects of the disease’s pathogenesis and prognosis. Evidence on the prognostic role of troponin and myocardial injury in Latin American hospitalized COVID-19 patients is still scarce. Objectives: To evaluate myocardial injury as independent predictor of in-hospital mortality and invasive mechanical ventilation support in hospitalized patients, from the Brazilian COVID-19 Registry. Methods: This cohort study is a substudy of the Brazilian COVID-19 Registry, conducted in 31 Brazilian hospitals of 17 cities, March-September 2020. Primary outcomes included in-hospital mortality and invasive mechanical ventilation support. Models for the primary outcomes were estimated by Poisson regression with robust variance, with statistical significance of p<0.05. Results: Of 2,925 patients (median age of 60 years [48-71], 57.1% men), 27.3% presented myocardial injury. The proportion of patients with comorbidities was higher among patients with cardiac injury (median 2 [1-2] vs. 1 [0-2]). Patients with myocardial injury had higher median levels of brain natriuretic peptide, lactate dehydrogenase, creatine phosphokinase, N-terminal pro-brain natriuretic peptide, and C-reactive protein than patients without myocardial injury. As independent predictors, C-reactive protein and platelet counts were related to the risk of death, and neutrophils and platelet counts were related to the risk of invasive mechanical ventilation support. Patients with high troponin levels presented a higher risk of death (RR 2.03, 95% CI 1.60-2.58) and invasive mechanical ventilation support (RR 1.87, 95% CI 1.57-2.23), when compared to those with normal troponin levels. Conclusion: Cardiac injury was an independent predictor of in-hospital mortality and the need for invasive mechanical ventilation support in hospitalized COVID-19 patients.
Lesão Miocárdica e Prognóstico em Pacientes Hospitalizados com COVID-19 no Brasil: Resultados do Registro Nacional de COVID-19
Keywords: Artificial Respiration; Coronavirus Infections; COVID-19; Mortality; Troponin